2017
DOI: 10.1021/acs.est.7b00392
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Nitrosococcus-Related Ammonia Oxidizing Bacteria Coincides with Extremely Low pH Values in Wastewater with High Ammonia Content

Abstract: Ammonia oxidation decreases the pH in wastewaters where alkalinity is limited relative to total ammonia. The activity of ammonia oxidizing bacteria (AOB), however, typically decreases with pH and often ceases completely in slightly acidic wastewaters. Nevertheless, nitrification at low pH has been reported in reactors treating human urine, but it has been unclear which organisms are involved. In this study, we followed the population dynamics of ammonia oxidizing organisms and reactor performance in synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 52 publications
5
56
0
Order By: Relevance
“…In Figure 5A, the pH values obtained in both influent and effluent are shown. They ranged between 6.8 and 7.6 in RVG and between 6.6 and 7.8 in PET, being within typical values of domestic wastewater [49]. The decreases in the pH of some of the data ( Figure 5B) are based on the removal of nitrogen that occurs in these systems, which causes a reduction in alkalinity [50].…”
Section: Flower Productionsupporting
confidence: 53%
“…In Figure 5A, the pH values obtained in both influent and effluent are shown. They ranged between 6.8 and 7.6 in RVG and between 6.6 and 7.8 in PET, being within typical values of domestic wastewater [49]. The decreases in the pH of some of the data ( Figure 5B) are based on the removal of nitrogen that occurs in these systems, which causes a reduction in alkalinity [50].…”
Section: Flower Productionsupporting
confidence: 53%
“…16S rRNA gene sequence-based phylogenetic analysis including searching the IMNGS platform ( https://www.imngs.org/ ) (Supplementary Fig. 2A ) revealed that the most closely related sequences were obtained from a refuse dump of leaf-cutter ants [ 36 ] (>99% identity), from a Finnish soil (PRJNA393827), and from a synthetic urine nitrification reactor [ 37 ], the closest cultured species was “ Ca . Ng.…”
Section: Resultsmentioning
confidence: 99%
“…terrae” [ 11 ] exhibited activity at pH of 4 and 5, respectively. In addition, Nitrosococcus -like species were found to be dominant in reactors treating human urine down to pH 2.2 [ 37 ]. The ability of oxidizing ammonia at low pH could be due to different adaptation mechanisms, metabolic flexibility, or by the cooperation between different species in the environment [ 5 , 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all mixed anaerobic cultures (MAnC 1, MAnC 2 and initial granular sludge used as inocula), some of the most abundant bacteria groups (class and genus) were Gammaproteobacteria (Nitrosococcus), Thermotogae ( M e s o t o g a ) , A c t i n o b a c t e r i a ( B r o o k l a w n i a ) , Deltaproteobacteria (Syntrophorhabdus) and Nitrospira and Anaerolineae uncultured genus. Nitrosococcus genus are Ammonia Oxidizing Bacteria (AOB), adapted to saline and acidic environments, regularly found in marine environments but less commonly detected in waste water treatment reactors (Fumasoli et al 2017). Mesotoga are frequently found in oil-polluted marine mesophilic anaerobic environments (Nesbø et al 2019).…”
Section: Anaerobic Microbial Profilementioning
confidence: 99%